The impact of listening strategy instruction on non-english major students listening comprehension = - Huỳnh, Thị Thanh Trúc (Can Tho University, 2009)
The purpose of the study was to evaluation to what extent listening strategy training affects the listening comprehension of non-English major student. It was hypothesized that the participants listening comprehension would be enhanced through the strategy instruction.